COMMUNITY HEALTH ASSISTANTS' PERCEPTIONS ABOUT THEIR ROLE IN THE FAMILY HEALTH STRATEGY - Daíla Timbó Oliveira; Paulo Jorge de Oliveira Ferreira; Larissa Bento de Araújo Mendonça; Helenir da Silva Oliveira (Universidade Federal do Paraná, 2012)
The study aimed to describe community health assistants' perception of their work processes in the Family Health Strategy. It is exploratory-descriptive research with a qualitative approach. Eight people participated, one from each of the Family Health Strategy units in the town of Quixadá in the state of Ceará. The data was collected in 2011 through interviews: the statements were submitted to close reading and Bardin's content analysis, from which six categories emerged. The study showed the existence of a positive relationship between community health assistants and the nurses in the health units, and that a shortage of materials hindered adequate performance of these workers' activities. It is fundamental that the nurse should be sensitive to identifying the difficulties mentioned by the assistants concerning their daily work routines.